2019
DOI: 10.1016/j.ymgmr.2019.100477
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies to ganglioside and Hep 2 in Gaucher, Niemann – Pick type C and Sanfilippo diseases

Abstract: Lysosomal Storage Diseases (LSDs) are rare genetic diseases, the majority of which are caused by specific lysosomal enzyme deficiencies and all are characterized by malfunctioning lysosomes. Lysosomes are key regulators of many different cellular processes and are vital for the function of the immune system. Several studies have shown the coexistence of LSDs and immune abnormalities. In this study, we investigated the presence of autoantibodies in the plasma of patients with Gaucher disease (GD; n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…2). The production of autoantibodies against the progressively accumulated gangliosides has been shown in the genetic disorders GM2 gangliosidoses [90], NPC, and Sanfilippo syndrome B [91], supporting the premise that elevation in host ganglioside levels can lead to antiganglioside antibody generation (Fig. 2).…”
Section: Associated Infectious Diseasesmentioning
confidence: 56%
“…2). The production of autoantibodies against the progressively accumulated gangliosides has been shown in the genetic disorders GM2 gangliosidoses [90], NPC, and Sanfilippo syndrome B [91], supporting the premise that elevation in host ganglioside levels can lead to antiganglioside antibody generation (Fig. 2).…”
Section: Associated Infectious Diseasesmentioning
confidence: 56%
“…A similar condition is thought to occur in lysosomal storage disease due to the genetic defects and the resultant excess peripheral organs (e.g., liver, spleen, lung, heart, kidneys, and lymph nodes) accumulation of distinct substrates (e.g., GC in Gaucher, Gb3 and Lyso Gb3 in Fabry, GM1 in GM1gangliosidosis, GM2 in Tay–Sachs and Sandhoff, Sph, GlycSph, Sm, and Ch in Niemann–Pick type C, Cer in Farber, GalSph in Krabbe, and CEs and TGs in Wolman diseases), which lead to the cellular activation and increased production of the growth factors, such as MCSF, GCSF, and GMCSF, which mobilize hematopoietic progenitors into the peripheral circulation [ 229 , 230 , 231 , 232 ]. This is supported here by the elevated level of growth factors (e.g., MCSF, GCSF, and GMCSF), chemoattractants (C3a, C5a, CCL2, CCL3, CCL4, CCL5, CCL10, CCL11, CCL12, CXCL1, CXCL9, CXCL10, CXCL11, and CXCL13), and the increased presence of MOs, granulocytes, MOs-differentiated Mϕs and DCs, T cells, NK cells, NKT cells, antibodies producing plasma B cells in circulation and the peripheral organs of the different lysosomal storage diseases [ 6 , 7 , 11 , 36 , 76 , 112 , 113 , 157 , 158 , 165 , 176 , 186 , 194 , 203 , 204 , 222 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 ]. The increased migration of several of such pro-inflammatory mediators into circulation may serve as a new set of biomarkers for diagnosing lysosomal storage diseases and evaluating the effectiveness of novel medications in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebella and cerebral cortex of Npc1 −/− mice have shown elevated levels of IFNα, IFNβ, TNFα, IL1α, IL1β, and the loss of Purkinje cells [ 157 , 161 , 162 , 163 , 164 ]. The plasma of patients with Niemann–Pick type C disease showed the presence of IgG and IgM antibodies to GM1, GM2, and GM3 [ 165 ]. The postmortem brain tissue (e.g., frontal cortex and cerebellum) from patients with NPC1 disease showed elevated levels of C3 and C4 [ 163 ].…”
Section: Niemann–pick Type C-disease-associated Neuroinflammation: De...mentioning
confidence: 99%
“…Many studies have reported an association between autoimmune phenomena and LSDs ( Rigante et al, 2017 ). Recently, autoantibodies in NPC have been reported in several studies ( Dimitriou et al, 2019 ; Chu et al, 2021 ). Herein, we reported two clinical cases of NPC in the form of cholestatic jaundice combined with immune activation in early infancy diagnosed by genetic analysis.…”
Section: Introductionmentioning
confidence: 99%